Strengthening Se’i Kupang Production through Kesambi Leaf Biobriquette Innovation, Financial Literacy, and Digital Marketing - Helda Marlin Ala; Mesri Welhelmina Nisriani Manafe; Herny Constantia Fanggidae; Jemmy Jonson Sula Dethan; Maromi Merlin Mbate (Amalee: Indonesian Journal of Community Research and Engagement, 2026)
Se’i, a traditional smoked meat from East Nusa Tenggara, Indonesia, has a strong cultural identity and economic potential; however, its production still relies on conventional firewood, resulting in inconsistent quality, energy inefficiency, and unstable production costs. This study aims to implement an integrated empowerment model that combines green energy innovation, financial literacy, and digital marketing to strengthen the sustainability of se’i micro and small enterprises (MSMEs) in Kupang City. The program was conducted using a Participatory Action Research (PAR) approach within a structured, integrated empowerment framework, including a baseline assessment, biomass briquette training and simulation, financial literacy workshops with SI-APIK digital bookkeeping implementation, digital marketing training, and a before–after evaluation. The results show a 22–28% reduction in fuel consumption per production cycle, improved stability of smoking temperature and product consistency, full adoption of simple financial reporting and cost-of-production calculation among partners, and increased digital engagement and transactions. The integration of biomass briquettes from Kesambi leaves, structured financial management, and data-driven digital marketing synergistically improved cost efficiency, managerial capacity, and market expansion. In conclusion, the integrated empowerment model effectively enhances production efficiency, financial transparency, and business competitiveness, offering a replicable framework for strengthening traditional food MSMEs through green innovation and digital transformation.